Effect of Pillar and Mesh Structure of Tetrahedral Amorphous Carbon (ta-C) Coatings on the Wear Properties and Fracture Toughness of the Coating - Mohd Muhyiddin Bin Mustafa (Japanese Society of Tribologists, 2019)
Wear by fracture is among the factors associated with the DLC coating failures in the tribological application. The current study investigated the link between the wear and the fracture-toughness on the novel Pillar and Mesh structure ta-C coatings, in addition to conventional ta-C coatings. The tribological properties of these coatings were examined under base-oil lubrication via ball-on-disk tribo-tester and micro indentation technique was used to characterize the fracture toughness. The wear track and the indentation mark were analyzed using the optical microscope, 3D laser microscope and FE-SEM. The friction coefficient for ta-C, Pillar ta-C and Mesh ta-C are within the range of 0.071 to 0.106. Mesh ta-C indicated the highest wear resistance, followed by the Pillar ta-C and conventional ta-C. Also, Mesh ta-C demonstrated the highest fracture-toughness value with 16.6 MPa·m1/2, followed by Pillar ta-C with 13.4 MPa·m1/2 in contrast to ta-C. Greater resistance to wear for ta-C with Pillar and Mesh structure was detected with an increased fracture-toughness and improvement in crack propagation inhibition. Moreover, the Pillar and Mesh ta-C provides superior rate of crack-energy dissipation as compared to the ta-C.